Design and Implementation of Smart Bench Integrated Solar Cell for Public Space Electricity Saving - Kango, Riklan; Hadiyanto, Hadiyanto; Pongtuluran, Ezra Hartarto (International Journal Papier Advance and Scientific Review, 2021)
The purpose of this research is to design a multifunctional garden bench integrated with solar panels. The bench product is created by utilizing sunlight as a source of electrical energy for the object features of the bench product. The implementation method for producing innovative bench products uses a research and development approach, including concept, design, collection of materials, assembly, and testing. The bench was tested to supply electricity to the LED lights and USB ports. Furthermore, analyzing statistical data the average value of; current, voltage, and power generated by the intelligent bench object. The study results present the primary resources needed for the design and implementation of intelligent bench products. Experiments show that a load of LED lights and USB station chargers depends on the percentage of battery batteries supplied from solar cells. The innovative bench is designed from hollow steel to support product construction efficiency and electronic effectiveness. In this way, we achieved our goal of designing and implementing a portable garden bench that could function in all open areas.